Penerapan Capital Asset Princing Model Terhadap Keputusan Investasi Saham - Gultom, Elida; Syafrina, Nova (Jurnal Ilmu Manajemen, 2022)
This study aims to determine efficient and inefficient stocks in banking sector companies on the Indonesia Stock Exchange for the 2019 -2021 period through the application of the Capital Asset Pricing Model (CAPM) method. The population in this study were all banking sector company shares registered for the 2019-2021 period, namely 46 companies with a total sample of 40 using a purposive sampling technique. The data source used was obtained from Yahoo Finance. Based on the results of the analysis, it was obtained that 30 company shares were included in the efficient condition category where Ri > E(Ri) and the remaining 10 company shares were included in the inefficient condition category where Ri < E(Ri). In this study also found that between beta and expected return there is an inverse relationship, where stocks of companies that have high beta have a low expected return and vice versa.